Influence of Humidity on the Electric Field, Filtration Efficiency, and Flow Velocity in Electret Filter Media: Direct Numerical Simulation - Daniel Stoll; Sergiy Antonyuk (Atmosphere, 2025)
Electret filter media are electrostatically charged during the manufacturing process to activate effective electrical separation mechanisms. In order to investigate the influence of humidity on these mechanisms, the electric field, and filtration efficiency, a Direct Numerical Simulation (DNS) study of the aerosol deposition within wetted fibrous nonwoven filter media used in masks was carried out. Initial experimental investigations determined key properties of the filter material, including porosity, fiber diameter, and surface charge density. Using Micro-Computed Tomography (µCT), preferred locations for droplet deposition within the filter were identified. Additional experiments quantified the amount of water absorbed by the filter medium and assessed its impact on the existing electric field. Numerical simulations examined various models with differing porosity and fiber diameter, incorporating different levels of water content to analyze the changes in the electric field, flow velocity, and resulting filtration efficiency. The results provide valuable insights into the significant effects of fiber change on filtration performance, demonstrating the electret filter’s ability to partially compensate for the negative impacts of water.